Repurposing pantoprazole and haloperidol as efflux pump inhibitors in azole resistant clinical Candida albicans and non-albicans isolates - Amira M. El-Ganiny; Hend A. Kamel; Nehal E. Yossef; Basem Mansour; Ahmed M. El-Baz (Elsevier, 2022)
Candida species have a major role in nosocomial infections leading to high morbidity and mortality. Increased resistance to various antifungals, especially azoles is a significant problem. One of the main mechanisms for azole resistance is the up-regulation of efflux pump genes including CDR1 and MDR1. In the current study, clinical Candida isolates were identified to the species level and the antifungal susceptibility (AFS) of different Candida species was determined by disk diffusion method. Furthermore, the main mechanisms of azole resistance were investigated. Finally, haloperidol and pantoprazole were tested for their potential synergistic effect against fluconazole-resistant isolates.One hundred and twenty-two Candida clinical isolates were used in this study. 70 isolates were Candida albicans (57.4%), the non-albicans Candida species include: C. krusei (20.5%), C. tropicalis (6.6%), C. parapsilosis (5.7%), C. dubliniensis (4.9%) and C. glabrata (4.9%). The AFS testing showed that resistance to fluconazole and voriconazole were 13.1% (n = 16) and 9.8% (n = 12), respectively. Among the 16 resistant isolates, eight isolates (50%) were strong biofilm producers, seven (43.8 %) formed intermediate biofilm and one had no biofilm. All resistant strains overexpressed efflux pumps. Using RT-PCR, the efflux genes CDR1, MDR1 and ABC2 were over-expressed in azole resistant isolates. Haloperidol-fluconazole and pantoprazole-fluconazole combinations reduced the MIC of fluconazole in resistant isolates. The current study showed an increase in azole resistance of Candida species. The majority of resistant isolates form biofilm, and overexpress efflux pumps. Pantoprazole and Haloperidol showed a noteworthy effect as efflux pump inhibitors which oppose the fluconazole resistance in different Candida species.